Supplementation of zinc from organic or inorganic source improves performance and antioxidant status of heat-distressed quail - Şahin, Kazım; Smith, MO; Onderci, M; Şahin, Nurhan; Gursu, MF; Küçük, Ömer (Elsevier, 2005)
Two sources of zinc [ZnSO4 center dot H2O or ZnPi-colinate (ZnPic)] supplementation were evaluated for their effects on performance, carcass weight, levels of malondialdehyde, and vitamins C, E, A in Japanese quail (Coturnix coturnix Japonica) exposed to high ambient temperature of 34 C. The birds (n = 360; 10-d-old) were randomly assigned to 12 treatment groups consisting of 3 replicates of 10 birds each in a 2 x 2 x 3 factorial arrangement of treatments (temperatures, zinc sources, zinc levels). Birds were kept in wire cages in a temperature-controlled room at either 22 C (thermoneutral) or 34 C (heat stress) for 8 h/d (0900 to 1700 h) until the end of study, and fed a basal (control) diet or the basal diet supplemented with either 30 or 60 mg of Zn as ZnSO4 center dot H2O or ZnPic/kg of diet. Heat exposure decreased (P = 0.001) live weight gain, feed intake, feed efficiency, and carcass weight when the basal diet was fed. A linear increase in feed intake (P = 0.01) and BW (P = 0.01), and improvement in feed efficiency (P = 0.01) and carcass weight (P <= 0.05) were found in zinc-supplemented quail reared under heat-stress conditions. Serum vitamin C (P = 0.04), E (P = 0.05), and cholesterol (P = 0.01) concentrations increased linearly, whereas malondialdehyde concentrations decreased linearly (P = 0.02) as dietary zinc sulfate and ZnPic supplementation increased. An interaction between dietary zinc sources, temperature, and levels of supplementation (P <= 0.05) for these parameters was detected. Serum vitamins C, E, and A concentrations were not different in supplemented birds reared at thermoneutral temperature. Supplementation with zinc improved carcass weight and antioxidant status of birds, and the effects of ZnPic were relatively greater than those of ZnSO4 center dot H2O in heat-stressed quail. Results of the present study suggest that supplementation with ZnPic could be considered to be more protective than ZnSO4-H2O by reducing the negative effects of oxidative stress induced by heat stress in quail.
Keywords: zinc picolinate; oxidative stress; performance; quail